Interfacing science and management for the Nylsvley Nature Reserve - Bestbier, Regina Xavier (My University, 2016)
Scientists possess knowledge and access to information that is critical to the management of natural resources, yet all too often this information is not effectively transferred and integrated into the management process. This lack of integration of scientific information into conservation management is a result of the barriers that exist between scientists and managers. Differences in the goals and reward systems of managers and scientists lead to managers feeling that scientists do not produce the "goods" that they require, Wh;l'! scientists claim that managers do not provide the questions for which they require answers. There is also a lack of forward thinking, goal-orientated management. As a result much of conservation management relies on irtuinvc, ad hoc decision-making which leads to It problem-by-problem curative approach (cf. adaptive management) as well as a lack of accountability and evaluation. The thesis of this study is that to overcome barriers between scientists and managers an interface must be developed between the two groups based on sound technology transfer principles (product development, transfer processes, consensus building, feedback, form and function) an,~ three primary elements - processes (which regulate the functioning of the interface), products (which are developed within the interface) and people (who 'drive' the interface), 'The overall aim of this study was to develop an interface to overcome barriers between scientists and managers at the Nylsvley Nature Reserve, Northern Province. Although much scientific information is availabJe for Nylsvley, it was not being transferred effectively to the managers. 1nere were no explicit protocols in place that identified operational goals to achieve the "vision" for the reserve. Also, there was very little 'organisational memory' to enable decision making at Nylsvley because of high staff turnover and poor information records. The interface developed in this study took the form of an 'objectives hierarchy'. The objectives hierarchy was developed to enable conservation organisations to translate policy (vision) into focused, purposeful action (operational goals), thus ensuring thatthe management is more goal orientated and providing scientists with the managers information requirements. This enables the scientists to provide the information that managers require, ir :le format that is most useful to them. Linked to the development of the objectives hierarchy for the Nylsvley Nature Reserve was the need for a mechanism to ensure 'organisational memory', Organisational memory is necessary to ensure continuity in the conservation management decision making environment, Thus a product from the interface was the Nylsvley Management Information System, a prototype computer program which ensures that the managers have access to information relevant for decision-making. Fundamental to the development of the interrace for Nylsvley was the development of informal collegia (networks), with contact inside and outside the conservation organisation. These informal collegia were necessary for overcoming bureaucratic resistence to change, and fc: building mutual respect and trust which was imperative for the development of a successful interface.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, for the Degree of Master of Science. Johannesburg, August 1998